Audit Performance Measurement Accurate Menggunakan ITIL Version 3 pada Domain Service Operation - Ferly Ardhy; Nur Aminudin; Asep Afandi; Mayang Indah Sari (STMIK IKMI Cirebon, 2021)
The Accurate system in a company as data bookkeeping aims to increase the effectiveness and efficiency of the data recording process, the performance of the Accurate system to avoid losing company data. The method used in this research is IT-IL Version 3 Domain Service Operation, this study usesÂ SWOT analysis within the company and it can be concluded that the value of all the factors can be specified for each item Strength: 2.32, Weakness: 0.71, Opportunity: 2 , 14, and Threat: 0.64. So it is known that the Strenght value above the Weakness value is the difference (+) 1.64 while the difference between the Opportunity and Threat values is 1.5. This research shows that the maturity level is at level 3 (Defined) with an average of 3,4. This shows that the resulting standard process is feasible..